Formation of Solonchak in the Area of the Discharged Ancient Brine Wells (Perm Krai, Russia) - Khayrulina, Elena; Mitrakova, Natalya; Poroshina, Natalya; Menshikova, Elena; Perminova, Anna (Frontiers in Environmental Science, 2022)
The change in soil-forming processes and, as a result, in the ecosystem due to nearly 300-year long outflow of highly saline waters from ancient brine wells is considered for Perm Krai in Russia for the first time. The study area is located in the high floodplain of the Usolka River valley. Sodium-chloride ancient brine wells with mineralization of about 30 g/L flow in streams over the soil surface and enter the Usolka River. The paper considers three soil types at various distances from a saline stream. The main pedogenic processes are sod-forming process and gleying in alluvial soils. Soils in Gleyic Fluvisols (background) - Gleyic Fluvisols (Sulfatic) (transition) - Solonchak (affected by sodium-chloride brines) series were studied in terms of occurring soil-forming processes. All studied soils are formed under hydromorphic conditions. It is evidenced by gleization. However, the morphological and physicochemical properties of the soils differ. The presence of water-soluble ions in the solonchak suggests that salinization is occurring. The sum of toxic salts was 0,94% which was several times higher than in the transition and background soils. The sodium adsorption ratio (SAR) ranged from 10.4 to 21.6, with a рН of 8.3—9.1. The saline soils were more alkaline (pH average 8.8 and 9.3) than the background soil (pH 8.1). SAR decreased significantly in the Solonchak – transition - background soil series from 16.9 to 0.7. The aforementioned observations, as well as physical properties of the saline soil, clearly show the entry of sodium into the solonchak adsorption complex, indicating the solonization process. The study area is characterized by the presence of salt-tolerant species of herbaceous plants and an obligate halophyte. Salicornia perennans Willd, a halophyte, was discovered in the wells discharge area at a distance of 0.2-1.5 m from saline streams. Analysis of the long-term impact of highly mineralized waters on the natural environment will aid in revealing and forecasting ecosystem changes caused by potash mining in Perm Krai for environmental risk assessment for new and existing potash enterprises.